Different methods of managing bluestem pastures - Smith, E.F.; Anderson, K.L.; Drake, C.L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This experiment was designed to determine the effect of different stocking rates, of deferred grazing, and of pasture burning on cattle performance, productivity of pastures, and range condition as determined by plant population changes. In addition to the yearling report, a summary of cattle gains for the past 13 years of the study is included.
Keywords: Beef; Bluestem pasture; Stocking rates; Deferred grazing